Human-nature Relationship in Riawani Elyta and Shabrina Q. S.’s Novel Rahasia Pelangi: an Ecocritical Approach - Fitrah Dwi Insany; Syifa Nur'ain; Windri Kartika Utami; M. Aidil Januar; Purwarno Purwarno (ITScience (Information Technology and Science), 2024)
The intricate interplay between humanity and the natural world is a fundamental aspect of our existence, essential for sustaining life and ensuring its continuity. Despite this inherent bond, the progression of human civilization, marked by advancements in science and technology, has often fostered a discordant and exploitative relationship with nature, precipitating environmental crises. In this context, our study delves into the nuanced portrayal of the human-nature dynamic in Riawani Elyta and Shabrina WS's novel, Rahasia Pelangi, through the lens of ecocriticism. Employing a descriptive qualitative approach, our research meticulously examines the multifaceted interactions between humans and nature as depicted in the novel, elucidating their profound implications. Our findings not only unveil a harmonious coexistence within the narrative but also shed light on the ecological repercussions of human activities on nature, thus underscoring the novel's ecological themes and its invaluable contributions to environmental discourse. By exploring the intricate relationship between humans and nature within the narrative framework of Rahasia Pelangi, this research seeks to deepen our understanding of the complexities inherent in our ecological interactions and foster meaningful dialogue towards a more sustainable future.